(untitled) (Journal of Governance and Development (JGD), 2014)
This is an evaluation study of an intervention program that seeks to mitigate the impact of climate change in Bayug Island, an 82-hectare delta at the estuaries of the Mandulog River in Iligan. During Typhoon Sendong on December 16, 2011, the entire island was inundated and many inhabitants perished. Originally estimated at 122.50 hectares, it shrunk into its present size due to erosion that allowed sea water to advance more than 100 meters inland in two decades. In 2010, a portion of its municipal waters was declared Marine Protected Area. In February 2011, the Bayug Mangrove, Rehabilitation and Reforestation Project of MSU-IIT was organized. In nine months, 21,000 propagules were planted along its coastline. A seaweed plantation was also established to provide alternative livelihood for ï¬ sherfolks. After Sendong, Iligan City declared Bayug Islalnd as danger zone based on the assessment of the Mines and Geo-Science Bureau, DENR, Region 10. Power and water reconnections were not permitted. But extension service volunteers of MSU-IIT returned in February 2012 to continue rehabilitating its denuded coastline. With the support of the Bureau of Fisheries and Aquatic Resources, 75,000 propagules were planted and six aquasilvi projects were established as of July 2014. On April 26, 2013, a City Ordinance establishing the Bayug Island Aquamarine Park was approved. Interventions in Bayug Island are designed to mitigate the impacts of Climate Change. However, typhoons like Sendong (2011), Pablo (2012), Zoraida (2013) and Agaton (2014) were great impediments. But for extension service volunteers, these are temporary setbacks that pushed for the improvement of strategies for disaster mitigation.